What if culture was nature all along? - Kirby, Vicki, 1950- (New materialisms (Edinburgh, Scotland), 2017)
New materialisms argue for a more science-friendly humanities, ventilating questions about methodology and subject matter and the importance of the non-human. However, these new sites of attention - climate, biology, affect, geology, animals and objects - tend to leverage their difference against language and the discursive. Similarly, questions about ontology have come to eclipse, and even eschew, those of epistemology. While this collection of essays is in kinship with this radical shake-up of how and what we study, the aim is to re-navigate what constitutes materiality. These efforts are encapsulated by a rewriting of the Derridean axiom, 'there is no outside text' as 'there is no outside nature.' What if nature has always been literate, numerate, social? And what happens to 'the human' if its exceptional identity and status is conceded quantum, non-local and ecological implication?